EXTH-70. IMMUNOTHERAPY REVERSES GLIOMA-DRIVEN DYSFUNCTION OF IMMUNE SYSTEM HOMEOSTASIS. (14th November 2022) - Dean, Bayli; Wildes, Tyler; Dean, Joseph; Shin, David; Francis, Connor; Sebastian, Mathew; Font, Laura Falceto; Moore, Ginger; Wummer, Brandon; Flores, Catherine
Abstract: BACKGROUND: Glioma-induced immune disfunction has been described in a limited number of studies, and here we further demonstrate that gliomas also interrupt the cellular differentiation programming and outcomes of hematopoietic stem cells (HSC) in the bone marrow. HSCs from glioma-bearing mice are re-programmed and driven towards expansion of myeloid lineage precursors myeloid-derived suppressor cells (MDSC) in secondary lymphoid organs. However, we found this is reversed by immunotherapy. Adoptive cellular therapy (ACT) has been demonstrably efficacious in multiple preclinical models of CNS malignancies, and here we describe how glioma-induced disfunction is reversed by this immunotherapeutic platform. METHODS: The impact of orthotopic KR158B glioma on HSCs was evaluated in an unbiased fashion using single cell RNAseq of lineage- cells and phenotypically using flow cytometry. Mature myeloid cell frequencies and function were also evaluated using flow cytometry. Finally, ACT containing total body irradiation, tumor-specific dendritic cells, tumor-reactive T cells, and HSCs isolated from glioma-bearing or non-tumor-bearing mice was used to evaluate cell fate differentiation and survival. RESULTS: We observed differential gene expression of HSCs in tumor-bearing versus healthy mice coupled with an expansion of myeloid lineage subsets in glioma-bearing mice. Interestingly, MDSCs from glioma-bearing mice demonstrated hyper suppressive capacity as compared to MDSCs from non-tumor-bearing hosts. Interestingly, treatment with ACT overcame the suppressive properties of glioma-bearing HSCs. When HSCs from tumor-bearing mice were transferred with ACT, we observed significant survival benefit and long-term cures in orthotopic glioma models compared with mice treated with ACT using non-glioma-bearing HSPCs. CONCLUSIONS: These findings demonstrate the suppressive disposition in HSCs from glioma-bearing hosts can be redirected using ACT for significant survival benefit. Collectively, these data demonstrate gliomas impact the hematopoietic compartment at the progenitor level to promote expansion of suppressive myeloid cells and their progenitors. However, ACT can overcome this bias and provide lasting anti-tumor effects.